THE INFLUENCE OF SERVICE QUALITY AND PRICES RICKY MOTOR WORKSHOP CUSTOMER SATISFACTION - Linata, Teda; Defrizal, Defrizal (Journal of Information System, Applied, Management, Accounting and Research, 2024)
In today's globalization period, there is a lot of competition, which is a significant challenge to manufacturers, because the enormous number of items or services available produces more intense competition in the corporate sector. This study aims to determine the effect of Service Quality (X1) and Price (X2) on Consumer Satisfaction (Y). This type of research use quantitative methods, namely questionnaire data from 100 respondents. To aid data analysis, this study makes use of statistical calculation tools, specifically the SPSS 20 program. The following tests are used: validity, reliability, multiple linear regression analysis, T test, F test, and determination coefficient. Based on the research findings, it is feasible to conclude that service quality and price have a significant impact on consumer satisfaction at Ricky Motor Workshop.